Desenvolvimento de rota sintética de novos materiais híbridos envolvendo o estudo dos parâmetros sintéticos - Campos, Nathália Rodrigues De (2022)
Herein, we report the synthesis of a uncommon secondary building block (hereinafter called Pre-I) as well as four new Co(II) coordination compounds containing the H2mpba2- ligand of formula:[Co2(H2mpba)3][Co(H2O)6]∙2H2O∙0,5DMSO(1), [Co2(H2mpba)3][Co(H2O)6] ∙3H2O∙0.5dpss (2), [Co2(H2mpba)2(H2O)4]∙4nH2O (3) e [Co2(H2mpba)2(CH3OH)2(H2O)2]n∙0.5nH2O∙2ndpss (4) with H4mpba = 1,3- phenylenebis(oxamic) acid and dpss= di(2-pyridyl)disulfide. For the compounds 1-4 two distinct synthetic methodologies were used, where the reaction of the N,N′-1,3- phenylenebis(oxamate) potassium salt (K2H2mpba) with cobalt(II) chloride hexahydrate afforded the compounds 1 and 3 while the reaction of the Pre-I building block with K2H2mpba salt yielded the compounds 2 and 4. The crystal structure elucidation showed that the Pre-I is a mononuclear cobalt(II) complex whose metal center is four-coordinated to two nitrogen atoms from the dpss ligand and two chloride atoms resulting in an unusual tetrahedral geometry. According to X-ray diffraction measurements for 1 and 2, there are two independent crystallography cobalt(II) centers coordinated to three H2mpba-2 ligands forming the triple-stranded dinuclear complex [Co2(H2mpba)3] 2- with negative charge balanced by the cationic coordination complex [Co(H2O)6] 2+ . For 3 and 4, a linear and a zigzag polymeric chain, respectively, is observed with cobalt(II) centers coordinated by H2mpba-2 ligands. Furthermore, crystallographic studies for 2 and 4 showed non-coordinated dpss molecules and the crystal packing driven by hydrogen bonds. In compound 2, a host-guest relationship is observed, since the dpss molecule is hosted in a structural hole. Thus, in this work, are detailed the synthesis and full characterization, and magneto-structural correlation studies of the Pre-I and of four new compounds based on cobalt(II).